2022
DOI: 10.33093/ijomfa.3.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Digital Readiness Analysis in Bandung Government for Smart City Implementation

Abstract: Digital readiness is the willing to switch to digital process workflows supported by technological innovation. It is changing the way business is conducted, creating unprecedented opportunities. Digital readiness is known as the pre-requisite for digital transformation in implementing smart governance to build a smart city. The purpose of this study is to explore the effect employing smart strategies and digital readiness of smart innovation initiatives on the governance of Bandung city government. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The study confirmed that IoE and IoT can help cities become more sustainable or green. Furthermore, elevated digital readiness translates to higher revenue and profitability, as digitally proficient companies attain significantly greater financial success compared to those with lower levels of digital preparedness [17]. [20].…”
Section: B Internet Of Things (Iot) and Green Certificationmentioning
confidence: 99%
“…The study confirmed that IoE and IoT can help cities become more sustainable or green. Furthermore, elevated digital readiness translates to higher revenue and profitability, as digitally proficient companies attain significantly greater financial success compared to those with lower levels of digital preparedness [17]. [20].…”
Section: B Internet Of Things (Iot) and Green Certificationmentioning
confidence: 99%